Developing a Project Management Dashboard for Telehealth Implementation (The Science Post, 2025)
In The rapid expansion of telehealth services, accelerated by the COVID-19 pandemic, presents significant challengesfor healthcare organizations in managing complex implementation projects. Effective project management toolstailored specifically for telehealth are lacking, resulting in coordination inefficiencies and increased risk of regulatorynon-compliance. This study proposes the development of a specialized project management dashboard designed tostreamline telehealth implementation by integrating real-time task tracking, regulatory monitoring, resourceallocation, and stakeholder communication into a unified platform. Using a mixed-methods approach, includingstakeholder surveys, system performance testing, and user feedback analysis, the dashboard was iteratively refined tomeet diverse user needs across clinical, administrative, and technical roles. Results demonstrate improved projectvisibility, enhanced collaboration, and increased adherence to compliance requirements. Key performance metricsindicate that the dashboard achieves high usability and system responsiveness, supporting agile project workflows.The study concludes with recommendations for further integration of predictive analytics and enhanced user trainingto maximize adoption. This research contributes a practical tool and a framework for managing telehealth projectsmore effectively, with implications for healthcare providers, IT teams, and policymakers aiming to expand digitalhealth services.